2010
DOI: 10.1016/j.jasms.2010.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amino acid side chains on apparent selective opening of cyclic b5 ions

Abstract: In this study, the possible influence of acidic, basic, and amide side chains on the opening of a putative macrocyclic b ion (b 5 ϩ ) intermediate was investigated. Collision induced dissociation (CID) of b 5 ions was studied using a group of hexapeptides in which amino acids with the side chains of interest occupied internal sequence positions. Further experiments were performed with permuted isomers of glutamine (Q) containing peptides to probe for sequence scrambling and whether the specific sequence site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 40 publications
6
38
1
Order By: Relevance
“…Upon collisional activation of an ornithine-containing peptide, the amine of the ornithine residue cyclizes via nucleophilic attack at the adjacent carbonyl group, resulting in a characteristic and preferential cleavage C-terminal to the carbonyl group. This phenomenon has been observed before, as lysine and many of its homologues have exhibited similar characteristics as a nucleophile previously [42][43][44][45].…”
Section: Introductionsupporting
confidence: 73%
“…Upon collisional activation of an ornithine-containing peptide, the amine of the ornithine residue cyclizes via nucleophilic attack at the adjacent carbonyl group, resulting in a characteristic and preferential cleavage C-terminal to the carbonyl group. This phenomenon has been observed before, as lysine and many of its homologues have exhibited similar characteristics as a nucleophile previously [42][43][44][45].…”
Section: Introductionsupporting
confidence: 73%
“…The mechanism of deletion of the internal lysine residue has been investigated by multi stage CID, chemical, and isotopic modification of the peptides and energy resolved CID techniques. Our results suggest that this selective deletion of the lysine residue from the interior of the peptide may not follow the sequence scrambling fragmentation pathway as reported earlier [21,[27][28][29][30][31][32]. A novel gas-phase peptide ion degradation pathway has been shown to be responsible for the specific loss of the internal lysine residues in the peptide.…”
Section: Introductionsupporting
confidence: 54%
“…Recent studies [21,[27][28][29][30][31][32] have shown that the b n -ions and their analogues of a peptide may undergo head-totail cyclization, forming a protonated cyclic intermediate through the nucleophilic attack by the N-terminal α-amino group on the carbonyl carbon of the C-terminal oxazolone ring. The authors showed that this cyclic protonated peptide intermediate [21,[27][28][29][30][31][32] undergoes ring opening at different amide bonds to form a series of the linear oxazolone terminated b n -ions of scrambled sequences. The cyclization and subsequent ring-opening process, was thus proposed to lead to scrambling of the original primary sequence of the b n -ions, which upon collisional activation could form the daughter ions corresponding to the neutral loss of an internal residue from the peptide.…”
Section: Deletion Of Internal Lysine Residuementioning
confidence: 99%
See 2 more Smart Citations